Meningkatkan Aksebilitas dan Navigasi Wisatawan melalui Aplikasi Mobile dan Web Berbasis GIS di Provinsi Kepulauan Bangka Belitung - Yanti, Febi; Zaliyanti, Zilfa; Fujianti, Linda; Josi, Ahmad (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Tourism plays an important role in the global economy, including in the Bangka Belitung Islands. However, information on tourism destinations here is still limited. Therefore, this exploration aims to create applications and websites based on Geographic Information Systems (GIS) to guide tourists in finding tourism destinations in the Bangka Belitung Islands. The GIS application makes it easier for tourists to access tourism information, increases interest in visiting, and makes finding locations easier. Through practical access via mobile applications and websites, this service helps local and foreign tourists. The development of mobile and website-based GIS applications is expected to overcome the limitations of previous tourism information systems in Bangka Belitung by utilizing Location Based Services (LBS). GIS technology, especially mobile GIS, allows easy access, updating, manipulation, analysis and display of geographic information. The conclusion of this research is that the development of GIS-based applications and websites using the LBS approach is expected to make a positive contribution in promoting tourism in the Bangka Belitung Islands Province, not only providing the required information but also enriching the experience of tourists.